Forecasting System For Increasing Crime At The Binjai City Police Station With The Application Of The Website-Based Exponential Smoothing Method - Lestari Riawan, Putri; Pardede, A M H (Yayasan Kita Menulis, 2023)
Binjai City is the closest city to the city of Medan, which is the heart of North Sumatra. As one of the closest cities to the city gate of Medan, there are many activities that require a lot of activities. In Binjai City there is a Binjai City Police Office which is located Jl. Sultan Hasanuddin No.1, Binjai City, North Sumatra. Based on crime data at the Binjai City Police Station, it shows that crime that occurs every day is constantly increasing. This is because several factors influence it, namely internal factors within oneself such as having a realistic mindset and so on while external factors such as economic level factors or low education levels that have an impact on the difficulty of finding jobs, uneven population density, very minimal salaries, urgent needs, supportive environmental situations, social inequality trigger envy and resentment, environmental associations that require costs and so on. When people are faced with such a situation, the thing that will come to their mind is how to get money to meet the needs of their families at all costs. So that it affects one's mentality and actions to commit criminal acts.Exponential smoothing method is a procedure that continuously improves forecasting with the average (smoothing = smoothing) past values of a time sequence data with. The Exponential smoothing method is a development of the Moving Averages method.